The Management of Fiqh Learning for Visually Impaired Students A Case Study at SLB A Aisyiyah Ponorogo - Agung Ramadhan; Zuhrotul Mufidah; Muhammad Rafif Yuliza Absa (Educan, 2026)
The management of Fiqh instruction for visually impaired students requires specific pedagogical adjustments to ensure that Islamic legal concepts are understood meaningfully. However, studies that specifically explore how planning, implementation, and evaluation are managed in special education contexts remain limited. This study looks at how visually impaired students at SLB A Aisyiyah Ponorogo are taught fiqh. The planning, execution, and assessment procedures in the educational context of the school were investigated using a qualitative case study methodology. Classroom observations, principal and Islamic Education teacher interviews, and documentation review were used to collect data. The interactive analytical paradigm of data reduction, data display, and conclusion drawing was used to evaluate the gathered data, and source and technique triangulation was used to increase the data's trustworthiness.. The study found that lesson planning refers to the Independent Curriculum for Special Education, although teachers make various adjustments to learning objectives, materials, instructional methods, and media based on students’ visual conditions. In classroom practice, teachers rely on verbal instruction, guided worship practice, classroom discussion, and accessible learning resources such as tactile media, audio materials, and Braille texts. Student learning outcomes are assessed through oral examinations and direct demonstrations of worship practices. These adaptive management practices contribute to improving students’ engagement, conceptual understanding, and independence in performing religious practices.